2001
DOI: 10.1152/physrev.2001.81.4.1415
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Their Functional Role in Vascular Endothelium

Abstract: Endothelial cells (EC) form a unique signal-transducing surface in the vascular system. The abundance of ion channels in the plasma membrane of these nonexcitable cells has raised questions about their functional role. This review presents evidence for the involvement of ion channels in endothelial cell functions controlled by intracellular Ca(2+) signals, such as the production and release of many vasoactive factors, e.g., nitric oxide and PGI(2). In addition, ion channels may be involved in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
855
2
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(912 citation statements)
references
References 433 publications
38
855
2
8
Order By: Relevance
“…However, based on our Ca 2 þ response data, we cannot exclude that the endothelial cells might also express mibefradil-sensitive Ca 2 þ channels. The current view is that endothelial cells do not express voltagedependent Ca 2 þ channels (Domenighetti et al, 1998;Nilius & Droogmans, 2001), although the opposite has also been suggested (Vinet & Vargas, 1999;Wu et al, 2003).…”
Section: Basal Characteristics Of the Kcl-induced Ca 2 þ Responsementioning
confidence: 88%
“…However, based on our Ca 2 þ response data, we cannot exclude that the endothelial cells might also express mibefradil-sensitive Ca 2 þ channels. The current view is that endothelial cells do not express voltagedependent Ca 2 þ channels (Domenighetti et al, 1998;Nilius & Droogmans, 2001), although the opposite has also been suggested (Vinet & Vargas, 1999;Wu et al, 2003).…”
Section: Basal Characteristics Of the Kcl-induced Ca 2 þ Responsementioning
confidence: 88%
“…Endothelial cell Ca 2+ has a crucial role in controlling vascular tone and homeostasis by releasing nitric oxide (NO), prostacyclin, and endothelium-derived hyperpolarizing factor (EDHF) [1][2][3][4][5][6] and affecting gene expression, angiogenesis, cell growth, and leukocyte migration [7,8], respectively. The level of cytoplasmic [Ca 2+ ] i can be modulated not only by the direct action of agonists and haemodynamic forces on the endothelial cells, but also indirectly by communication from surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ -activated K channels including small-conductance, intermediate-conductance and bigconductance have been shown to be expressed in endothelial cells [1][2][3][4][5]. Although Ca 2+ -activated small conductance and intermediate-conductance K channels are mainly responsible for determining the membrane potential under basal conditions [3], BK channels may also be involved in regulating the membrane potential of endothelial cells because BK channels have a high channel conductance.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ca 2+ -activated small conductance and intermediate-conductance K channels are mainly responsible for determining the membrane potential under basal conditions [3], BK channels may also be involved in regulating the membrane potential of endothelial cells because BK channels have a high channel conductance. It is conceivable that BK channels could play an important role in participating in generating the membrane potential in endothelial cells when they are activated [3]. Indeed, it has been shown that expression of BK channels in cultured endothelial cells caused a transient hyperpolarization induced by ATP [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation